Semen Parameters Can be Used as a Credible Marker with Doppler Ultrasonography in the Diagnosis of Subclinical Varicocele Cases - Tulay Irez; Bahar Sarikaya; Mine Erguven; Emre Salabas (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: The link between varicoceles and male infertility has been a problem of debate for more than half a century. A substantial amount of data about varicocelectomies’ effects has been provided, but inadequate study designs and heterogeneity of current studies make these data rarely conclusive. This article investigates whether semen and sperm analysis in subclinical varicocele patients without any clinical signs diagnosed by Doppler Ultrasonography (USG) can be used as a diagnostic tool.